Stock assessment of the Indian squid Loligo duvauceli Orbigny - Meiyappan, M M; Srinath, M; Nair, K Prabhakaran; Rao, K Satyanarayana; Sarvesan, R; Rao, G Syda; Mohamed, K S; Vidyasagar, Kuber; Sundaram, K S; Lipton, A P; Natarajan, P; Radhakrishnan, G; et al. (Indian Journal of Fisheries, 2011)
The present status of the fishery, biology and stock assessment of the India squid Loligo duvauceli Orbigny was studied, based on the data collected at different centres on both the coasts of India for 1979-1989. The production had increased by over 280% in 3 states on the west coast, viz. Kerala, Maharashtra and Gujarat. These states accounted for about 80% of the all-India squid production (23,941 t in 1989). Trawl is the main gear, taking 86% of the total squid landings. The fishing effort and squid catch on the east coast was comparatively more in the third quarter. On the west coast the first and fourth quartÂ«^ were the most productive. The natural mortality rates calculated based on different levels of M/K values (1.5, 2, 2.5 and 3) showed that they ranged from 1.35 to 2.7 for males and from 1.95 to 3.9 tor females on the east coast; from 1.2 to 2.4 for males and from 1.65 to 3.3 for females on the west coast. On both the coasts the values for females were higher than for males. The maximum fishing mortality (1.2 - 4.3) under different M/K values for males was at the size of 85 mm, and for females (5.8 - 6.7) at 175 mm on the east coast. For the west coast males the maximum fishing mortality (3.3 - 4.3) was at the size of 230 mm and for females (2.3 - 3.8) at 130 mm. The standing stock of males was higher than that of females on the east coast, with a reverse order on the west coast. The MSY and mean biomass at different M/K levels were also estimated for males and females separately for each coast. The present level of exploitation was at the optimum level on both the coasts.